Kenyamanan termal berdasarkan aktivitas penghuni di unit hunian Rumah Susun Jatinegara Barat - Ulinata; Napitupulu, Sally Septania; Merah, Adinda Garda; Dandy, Kristoforus (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
The Special Capital Region (DKI) of Jakarta is an area that experiences population growth every year, which raises the number of housing-related needs and reduces the amount of available vacant land for housing. In order to get around the lack of land for housing, a plan for flats—like the West Jatinegara Flats—must be implemented. The spaces in an apartment that are designed by an architect are required to produce a design that takes into account the comfort factor of the space for the occupants or users in addition to aesthetics. Residents feel comfortable if they are at a thermal temperature of between 22.8℃-25.8℃ with humidity of 70%. The study,